Group Procedures for Decreasing Problem Behavior Displayed by Detained Adolescents. Issue 5 (September 2019) - McDougale, Cassidy B.; Coon, Jodi C.; Richling, Sarah M.; O'Rourke, Soracha; Rapp, John T.; Thompson, Kelli R.; Burkhart, Barry R.
As one component of providing treatment in a residential facility, Brogan, Falligant, and Rapp decreased problem behavior by two groups of detained adolescents using group contingency procedures. The current series of studies evaluated the extent to which group procedures could be extended to other contexts within a residential facility. In Study 1, fixed-time delivery of attention by dormitory staff decreased problem behavior displayed by a group of five to 11 detained adolescents during free periods. In Study 2, rules from a therapist plus contingencies for following those rules increased appropriate line walking during specific transition periods. Subsequently, rules alone maintained appropriate line walking, however, direct training was required to produce appropriate line walking during other transitions. Measures of social validity indicated the procedures and outcomes in both studies were acceptable to facility personnel.